2006
DOI: 10.1021/es0618999
|View full text |Cite
|
Sign up to set email alerts
|

Perfluorinated Chemicals in the Arctic Atmosphere

Abstract: Twenty high-volume air samples were collected during a crossing of the North Atlantic and Canadian Archipelago in July 2005 to investigate air concentrations of fluorotelomer alcohols (FTOHs) and perfluoalkyl sulfonamido ethanols (PFASs). These commercial chemicals are widely used as surface treatments and are believed to be precursors for perfluorocarboxylic acids (PFCAs) and perfluorooctane sulfonate (PFOS) that accumulate in humans and biota, including those from remote arctic regions. The highest concentra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

22
251
8

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 281 publications
(281 citation statements)
references
References 31 publications
22
251
8
Order By: Relevance
“…These values are comparable to or a bit higher than those in the Atlantic Ocean and the Arctic region. 4,17 However, clear differences in the PFC mixtures were seen between the three sites (see Figure 4), reflecting the regional differences discussed above. Figure 1 shows the average back-trajectories at 100 m AGL (above ground level) during the sampling period at the three sites.…”
Section: Articlementioning
confidence: 77%
See 1 more Smart Citation
“…These values are comparable to or a bit higher than those in the Atlantic Ocean and the Arctic region. 4,17 However, clear differences in the PFC mixtures were seen between the three sites (see Figure 4), reflecting the regional differences discussed above. Figure 1 shows the average back-trajectories at 100 m AGL (above ground level) during the sampling period at the three sites.…”
Section: Articlementioning
confidence: 77%
“…25 Concentrations measured at the background sites (C17 and C18) were comparable to remote sites over the Atlantic Ocean 26 and in the Arctic. 17 FT Acrylates. Measurements of FTAs have been attempted in a few studies.…”
Section: ' Introductionmentioning
confidence: 99%
“…Perfluorooctanoic acid (PFOA) is a perfluorinated chemical that is gradually becoming the focus of considerable concern due to its resistance to natural degradation [1] and its widespread occurrence in ecological systems [2]. This chemical is inevitably released into environmental compartments with the large-scale production of PFOA and its precursors, such as fluorotelomer alcohols and perfluoroalkyl sulfonamides [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, these chemicals were found to have a wide distribution in the ambient atmosphere (Jahnke et al, 2007;Stock et al, 2004), including in indoor air and dust (Shoeib et al, 2006;Strynar and Lindstrom, 2008). Previous studies have found that FTOHs Toxicology and Applied Pharmacology 247 (2010) [222][223][224][225][226][227][228] can be biotransformed to perfluorinated acids (Wang et al, , 2009.…”
Section: Introductionmentioning
confidence: 99%